Television's top 100 : the most-watched American broadcasts, 1960-2010 - Hyatt, Wesley (McFarland & Co., 2012)
"Here you will find the inside stories about the most popular specials, movies, miniseries and series episodes in television history, from Number 100 to the top of the list. Weekly series and recurring specials are represented by their highest-rated individual entry. Included are appendices with facts and figures about the Top 100, and chronological listing of programs"--Provided by publisher.